Pengaruh Kualitas Produk, Citra Merek dan Harga terhadap Keputusan Pembelian Monitor Aoc 24g2e - Mega; Marcellia Susan (SAFE-Network, 2023)
The increasing demand from gamers for top-notch monitors is fueling rapid growth and intense competition in the monitor industry. According to data released by the International Data Corporation (IDC), Admiral Overseas Corporation AOC has emerged as a global leader in gaming monitor popularity. This achievement can be attributed to AOC's design strategy, which focuses on continuous product development and incorporates feedback from professional gaming enthusiasts. For companies, consumer purchasing decisions play a pivotal role as they contribute to revenue generation and help maintain competitive positions in the market. Several factors influence consumer purchasing decisions, including product quality, brand image, and price. This research aims to examine the characteristics and impact of product quality, brand image, price, and purchase decisions specifically related to the AOC 24G2E Monitor. The research employs a quantitative approach, utilizing descriptive analysis and multiple linear regression analysis as the analytical techniques. Primary data from 100 consumers of the AOC 24G2E Monitor were collected through a questionnaire, employing purposive sampling. The analysis results indicate that product quality, brand image, and price significantly influence the purchase decisions for the AOC 24G2E Monitor, with a coefficient of determination of 89.3%.